Gethsemane in the Visual Arts: From Textual to Visual Exegesis - Burnet, Régis (Die Bibel in der Kunst, 2024)
This article explores the complexities and challenges of the representation of the biblical episode of the Agony in Gethsemane. Beginning with the recognition of the inherent differences between textual and visual arts, it highlights how visual representations must contend with the metaphysical and temporal dimensions that are central to the Gethsemane narrative. The synoptic Gospels provide the primary textual basis for these representations, focusing on Jesus’ intense prayer and the disciples’ failure to remain vigilant. The article examines how artists have historically navigated the challenge of depicting an event that is intimate and eschatological in nature. It discusses the evolution of these representations, from early Christian art that emphasized Christ’s divinity to later works that increasingly focused on his humanity and psychological suffering. The use of space, symbolism, and specific motifs, such as the cup, the angel, and the sweat of blood, are analyzed to show how painters have pictured the unrepresentable aspects of this episode.